2006
DOI: 10.1099/vir.0.81993-0
|View full text |Cite
|
Sign up to set email alerts
|

Potato virus X RNA-mediated assembly of single-tailed ternary ‘coat protein–RNA–movement protein’ complexes

Abstract: Different models have been proposed for the nature of the potexvirus transport form that moves from cell to cell over the infected plant: (i) genomic RNA moves as native virions; or (ii) in vitro-assembled non-virion ribonucleoprotein (RNP) complexes consisting of viral RNA, coat protein (CP) and movement protein (MP), termed TGBp1, serve as the transport form in vivo. As the structure of these RNPs has not been elucidated, the products assembled in vitro from potato virus X (PVX) RNA, CP and TGBp1 were charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 35 publications
1
72
0
1
Order By: Relevance
“…The TGB proteins are highly conserved in members of the genera Potexvirus, Hordeivirus, Benyvirus and Carlavirus [6,15,23]. ORF5 encodes the capsid protein (CP) with an estimated molecular mass of 25 kDa and plays an significant role in cell-to-cell movement of PVX particles and translational regulation of the PVX RNA genome [10,14]. The CP gene is widely used for identification and classification of PVX isolates [3,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The TGB proteins are highly conserved in members of the genera Potexvirus, Hordeivirus, Benyvirus and Carlavirus [6,15,23]. ORF5 encodes the capsid protein (CP) with an estimated molecular mass of 25 kDa and plays an significant role in cell-to-cell movement of PVX particles and translational regulation of the PVX RNA genome [10,14]. The CP gene is widely used for identification and classification of PVX isolates [3,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the CP localization by itself does not exclude the nucleus as the compartment where recognition could take place. It is tempting to speculate that the roles the CP fulfills in PVX replication and cell-cell movement of viral RNA Fedorkin et al, 2001;Karpova et al, 2006;Bamunusinghe et al, 2009), which have been associated with the endomembrane system and plasmodesmata, form the ground for its recognition in the cytoplasm.…”
Section: Rx1 Is Activated In the Cytoplasmic Compartmentmentioning
confidence: 99%
“…Previous studies have shown that the PVX isolates can be classified into two lineages, Eurasia and America, which correspond to their geographical origin [22,24,44,45]. PVX is well-known as a model for understanding pathogen-host interaction [4,14,20] and efforts in recent years have established good knowledge about genetic basis of resistance and the genetic system controlling behavior of the pathogen [2,21,32].…”
Section: Introductionmentioning
confidence: 99%